Cases of Subconjunctival Hemorrhage after a Joy Ride - Tanveer A. Chaudhry, Khabir Ahmad, Roomasa Channa, Sana Shoukat Memon (Pakistan Journal of Ophthalmology, 2009)
Subconjunctival hemorrhage is a benign condition that mostly resolves spontaneously on its own, even though it may be very alarming for the patients. Multiple causes of subconjunctival hemorrhage-including local trauma, acute conjunctivitis and systemic hypertension have been reported in literature1,2.